Analgesic Effects of Ketamine Ointment in Patients With Complex Regional Pain Syndrome Type 1. Issue 5 (1st September 2002) - Ushida, Takahiro; Tani, Toshikazu; Kanbara, Tetsuya; Zinchuk, Vadim S.; Kawasaki, Motohiro; Yamamoto, Hiroshi
Abstract : Objective: Ketamine hydrochloride (KET), an agent used for general anesthesia, has local anesthetic effects and N -methyl-d-aspartate (NMDA) receptor antagonist action. Because recent studies emphasized the role of peripherally distributed NMDA receptors in processing the nociceptive information, we investigated whether peripheral application of the ointment containing KET is able to attenuate the symptoms of local neuropathic pain. Case Reports: We applied ointment containing KET (0.25%-1.5%) to the affected area on limbs in 5 patients with complex regional pain syndrome type I (CRPS I) and in 2 patients with type II (CRPS II). One to 2 weeks later, we observed improvement of the report of pain intensity, measured by the visual analog scale, in 4 patients with acute early dystrophic stage of CRPS I. Swelling of the affected limbs subsided as well. No apparent changes were noticed in 1 patient with chronic atrophic stage of CRPS I and in both patients with CRPS II. Conclusion: Topical application of KET appears to be beneficial for the patients with acute early dystrophic stage of CRPS I because of either its local anesthetic effect or NMDA receptor antagonist action. Patients with chronic atrophic stage of CRPS I and CRPS II patients do not appear to respond to this treatment.